Pengembangan Lembar Kerja Siswa (LKS) Berbasis Discovery Learning pada Mata Pelajaran IPA - Anisa Nadila; Eka Lokaria; Donni Pestalozi (Journal of Elementary School (JOES), 2023)
This study aims to develop a product in the form of discovery learning-based student worksheets (LKS) in science learning for fifth grade students at SDN 63 Lubuklinggau according to the 2013 curriculum and to produce student worksheets that are valid, practical and effective for use in learning. This research is a development research with a four-D development model. Based on the results of the assessment analysis by the three experts, namely: 0.81 media experts, 0.75 language experts, 0.90 material experts, from the three validation analysis results obtained an average validation of 0.82 this indicates that student worksheets (LKS) based on discovery learning in science learning meets very valid criteria. While the results of the research on teacher practicality sheets obtained an average of 92% and students with one to one trials consisting of 3 people obtained an average of 93%, then small group trials consisting of 6 people obtained an average of 90%, from the three trial results obtained an average practicality of 92%, this indicates that student worksheets (LKS) based on discovery learning in science learning meet the very practical criteria. Then the effectiveness results obtained an N-gain value of 0.8 in the high category. It can be concluded that the student worksheets (LKS) based on discovery learning are valid, practical, and effective. Thus, it can be stated that discovery learning-based student worksheets (LKS) are appropriate for use in thematic learning of fourth grade elementary school students. Keywords: Development, LKS, Discovery Learning.